2013
DOI: 10.3844/ojbsci.2013.66.71
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis of Urothelial Bladder Cancers

Abstract: Malignant cancers of urinary bladder are the second most common malignancy of the urinary tract and the fourth most common malignancy in general, especially in men. The aim of this study was a retrospective analysis of selected markers (p53, Ki-67 and E-cadherin) of urinary bladder cancers from the Department of Urology in Bratislava, Slovak Republic between years 2007 and 2009. We analysed 244 patients (202 males, 42 females) with diagnosed bladder cancer via cystoscopy and subsequent transurethral resection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Statistically, the overexpression of Bcl2 in relation to stage was not significant confirming the observation by others. 9,14,15,17 On the contrary other studies had reported significant correlation with higher stages. 10,12,13,20 (13) 2013…”
Section: 8mentioning
confidence: 96%
See 2 more Smart Citations
“…Statistically, the overexpression of Bcl2 in relation to stage was not significant confirming the observation by others. 9,14,15,17 On the contrary other studies had reported significant correlation with higher stages. 10,12,13,20 (13) 2013…”
Section: 8mentioning
confidence: 96%
“…Oncogenes may contribute to transformation and progression of tumors by being either overexpressed or mutated to produce an oncoprotein. 9 One of the more important mechanisms by which oncogenes are overexpressed in bladder cancer is through gene amplification. 9 Overexpression of Bcl-2 has been reported in a wide variety of cancers including those of prostate, colorectum, lung, kidney, and bladder.…”
Section: 8mentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis, therapy, and prognosis of NMIBC suffer from an unpredictable recurrence rate and a chance of progression, while MIBC often represents aggressive neoplasms with peripheral invasion, metastases, and poor response to treatment (Cho et al 2009 ; Fukumoto et al 2016 ). Classic immunohistochemical analysis of cancer tissue is widely utilized, but studies show that this method is unsuitable for the use of prediction of recurrence and progression (Bevizova et al 2013 ; Repiska et al 2010 ). Over the last few years, the European Association of Urology (EAU) has slowly adopted and implemented molecular markers into BC diagnosis, but they are not yet suitable for routine application, and cystoscopy in combination with cytology is still the gold standard (EAU Guidelines 2020 , 2021 , 2022 ).…”
Section: Introductionmentioning
confidence: 99%